Students’ Conscientiousness and Environments at the Civil Engeneering Education Department of Engineering Faculty of Yogyakarta State University - Suparman Suparman (LPPM UNY, 2011)
This study aims at revealing the conscientiousness and environments of students (CES) at the Engineering Faculty (EF) of Yogyakarta State University (YSU). A sample of 160 students was chosen randomly from a population of 600 students. The data of the study were collected by questionnaires. The instrument was a Likert-scale model with four options. The data were analyzed by descriptive statistics. The research results are as follows. (1) The conscientousness of Civil Engineering and Planning Education students of EFYSU is quite high (69.5%). In details, the conscientiousness of S1 (Strata 1 Level) students is high (69.7%), D3 (Diploma 3 Level) students is quite high (69.3%), and the male students tend to be higher on the conscientousness than female students (66.9% vs. 62.4%). (2) The students environment is conducive enough (63.7%). In details, the environment is conducive for S1 students (65.1%), fairly conducive (62.4%) for D3 students, and the environments for male students tend to be more conducive than female students (64.6% vs. 58.5%). (3) The unconducive environment of students is low (35.3%). In details, the unconducive environment for S1 students is low (32.7%) for D3 students is low (37.7%), and the unconducive environment for male students tend to be higher than female students (52.7% vs. 31.7%).